Investigating interactive metadiscourse markers in research article discussions published in varied journal levels (local, national, and international) - Wulandari, Mega Fitri; Arsyad, Safnil; Yunita, Wisma (Politeknik Negeri Bali, 2024)
Interactive metadiscourse markers in the discussion section of a journal play a crucial role in engaging the reader and facilitating a more dynamic interaction. In a discussion journal section, interactive metadiscourse markers may include phrases or expressions that invite the reader to consider alternative viewpoints, respond to the presented ideas, or reflect on the implications of the research findings. This research investigated interactive metadiscourse markers in research article discussion of language teaching within 30 articles published in local, national, and international journals. A mixed-methods approach was adopted and the instrument used in this research was a checklist designed to analyze interactive metadiscourse. The result of the inter-rater agreement of the co-rater and researcher indicated a kappa value of 90.2% (co-rater and researcher respectively) because it shows excellent agreement (above 80%). It shows that the highest frequency used of interactive metadiscourse category is transitions markers in the three-level journals. Evidential markers took the second position in frequency used followed by code glossed in third frequency. Endophoric markers and frame markers are less used by the writers in the article discussions. The research articles published in international reputable journals show the highest number of using interactive metadiscourse devices than the articles published in local and national journals.